ENGLISH VOCABULARY RETENTION ON MOVIE SERIES WITH L1 AND ENGLISH SUBTITLES: THE ROLE OF VOCABULARY LEVEL AND FREQUENCY - Aziz, Zulfadli A; Mustafa, Faisal; Yulia, Miga (LLT Journal: A Journal on Language and Language Teaching, 2024)
Regardless of its significance for language learning, the effect of a movie subtitle on vocabulary retention was rarely investigated. This study aimed to compare the impact of the subtitles in the first language (L1, Indonesian) and English as the target language on the learners’ vocabulary retention after watching seven episodes of a movie series. Sixty pre-service English teachers were divided into L1 and English subtitle groups to watch all episodes of the series in three non-consecutive days with a randomly pre-determined subtitle. They completed a vocabulary test before the experiment, immediately after the experiment, and one week after the experiment. The tests comprise words from the 2nd to 11th 1,000 level appearing at least five times across all episodes. The data were analyzed using inferential statistical analysis. The results show that vocabulary improvement was significant in both groups without any differences between groups. Still, the English subtitle group outperformed L1 subtitle counterparts for vocabulary between the 2nd and 9th 1,000 level and vocabulary appearing between five and ten times. These results suggest that movie series with both L1 and English subtitles can be used to expose students to English vocabulary, but a target language subtitle was superior for vocabulary retention. Therefore, English language learners are suggested to watch captioned English movies for maximum impact on vocabulary acquisition.